2016
DOI: 10.1016/j.survophthal.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news: A communication competency for ophthalmology training programs

Abstract: As the ophthalmology accreditation system undergoes major changes, training programs must evaluate residents in the 6 core competencies, including appropriately communicating bad news. Although the literature is replete with recommendations for breaking bad news across various non-ophthalmology specialties, no formal training programs exist for ophthalmology. There are many valuable lessons to be learned from our non-ophthalmology colleagues regarding this important skill. We examine the historic basis for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…8 In another study by Hilkert et al, 34 participants (76%) similarly agreed that ophthalmologists would benefit from a structured approach to training, and 73% felt that residency would be the ideal setting. 9 In our study, a large proportion of physicians, mostly residents, had already received formal training in breaking bad news, and this experience most often occurred during medical school. In contrast, one-third of board-certified ophthalmologists in our study had never attended formal training in breaking bad news.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…8 In another study by Hilkert et al, 34 participants (76%) similarly agreed that ophthalmologists would benefit from a structured approach to training, and 73% felt that residency would be the ideal setting. 9 In our study, a large proportion of physicians, mostly residents, had already received formal training in breaking bad news, and this experience most often occurred during medical school. In contrast, one-third of board-certified ophthalmologists in our study had never attended formal training in breaking bad news.…”
Section: Discussionmentioning
confidence: 82%
“…In a small pilot study involving 11 ophthalmology residents at a single academic center, residents who were taught how to use the SPIKES protocol to deliver bad news had increased confidence in delivering bad news after the intervention. 9 Larger studies involving more physicians and patients at multiple academic centers are needed to assess the benefit of a formal education plan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPIKES (11) protocol includes 6 steps: (1) Setting up the environment; (2) assessing the patient's Perception of his/her condition; (3) Inviting the patient to define which information he/she would like to receive; (4) providing the required Knowledge to the patient; (5) addressing the patient's Emotions with empathic responses; and (6) providing a Summary of treatment options and future plans. SPIKES was originally used in oncology but gradually shifted to other fields of medicine, including infectious diseases, gynecology, neurology, and ophthalmology (11,(15)(16)(17)(18). Previous studies have identified the absence of specific guidelines for sharing difficult news in psychiatry (19) and showed the need for such protocols (20), yet the SPIKES model has not yet been empirically studied in psychiatry (21).…”
Section: Introductionmentioning
confidence: 99%